Challenging Structural Racism and Violence in Policy and Practice for Indigenous Families Experiencing Homelessness in Alberta, Canada - Rodriguez, Cathryn; Henderson, Rita; Lucas, Katelyn; Bristowe, Sean; Bromley, Jackie; Chief Moon, Monica; Fraser-Celin, Valli; Milaney, Katrina (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Background: Canada’s settler history and legacy impacts of colonialization mean that policy is grounded in Eurocentric ideals which exacerbate vulnerabilities for Indigenous families due to gendered and racialized experiences. Objectives: Our purpose was to understand the experiences of Indigenous women as they try and secure safe affordable housing for themselves and their children. Methods: We utilized a community-based approach and interviewed 12 urban Indigenous women with current or recent experiences of homelessness. Results: Structural violence and racism manifested in three ways: trauma leads to homelessness which leads to trauma; families are trapped in dependency; the search for housing leads to fear of violence. Conclusion: The existence of multiple polices and frameworks to prevent human rights and housing violations are inadequate in protecting Indigenous women and children from racism and violence. An anti-colonial approach is necessary to review and align mainstream policy. This work must be led by lived experience experts.